2012
DOI: 10.5007/1980-0037.2012v14n6p671
|View full text |Cite
|
Sign up to set email alerts
|

Monitoramento da carga interna de treinamento em jogadores de futsal ao longo de uma temporada

Abstract: -There is a need for studies on methods for control of load and description of periodization in futsal teams. The objective of this study was to report and analyze the internal training load in a macrocycle of futsal using the session rating of perceived exertion (session-RPE) method. The sample consisted of 13 athletes of the National League. We calculated the total weekly training load (TWTL), monotony and strain over 37 weeks. Using the paired Student's t Test, the preparation period (PP) showed higher TWTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
2
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 22 publications
0
22
2
4
Order By: Relevance
“…According to Foster et al 10 , the PSE-session method is inexpensive and easy to apply, in addition to revealing sensitivity to changes in training loads. Corroborating the results obtained by Foster et al, 10 Miloski et al 3 showed that the internal training load analyzed by the PSE-session method varied depending on the external training load throughout the season in indoor soccer players. Therefore, considering that the findings of this study for the tapering stage showed decreased internal load for the EG, it could be inferred that the linear tapering strategy can be effective in reducing the stress generated by training young indoor soccer athletes.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…According to Foster et al 10 , the PSE-session method is inexpensive and easy to apply, in addition to revealing sensitivity to changes in training loads. Corroborating the results obtained by Foster et al, 10 Miloski et al 3 showed that the internal training load analyzed by the PSE-session method varied depending on the external training load throughout the season in indoor soccer players. Therefore, considering that the findings of this study for the tapering stage showed decreased internal load for the EG, it could be inferred that the linear tapering strategy can be effective in reducing the stress generated by training young indoor soccer athletes.…”
Section: Discussionmentioning
confidence: 66%
“…The weekly training load was obtained from the sum of daily loads divided by five (number of weekly training sessions). The load of each mesocycle (preparatory, competitive and tapering) was calculated from the sum of weekly loads divided by four (amount of microcycles per mesocycle), according to methodology adopted in another research 3 . It is noteworthy that athletes became familiar with the PSE-session method for a period of 30 days prior to the study.…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations